Solid solutions of the (1-x)Ba(Ti0.50Sn0.50)O3∙xPbTiO3 system: Preparation, structural and dielectric characterization. Issue 22 (15th November 2021) - Bush, Alexandr; Kozlov, Vladislav; Stepanov, Alexandr; Sirotinkin, Vladimir
Abstract: Ceramic samples of the (1-x)BaTi0.5 Sn0.5 O3 ∙xPbTiO3 system with 0 ≤ x ≤ 1 were synthesized by solid-state reaction method. The samples were characterized by X-ray diffraction, dielectric measurements, and thermally stimulated depolarization currents (TSDCs) technique. It was established that the solid solutions with the perovskite structure were formed in the entire range of the compositions. The structure symmetry of the solid solutions changes from cubic (x ≤ 0.30) to tetragonal (x > 0.47) with increasing PbTiO3 content. The samples with 0.30 < x ≤ 0.47 contained mixtures of the tetragonal and cubic phases. The solid solutions exhibit a pronounced aging effect. This effect manifests itself as non-reproducible maxima in the temperature-dependent spectra of the dielectric permittivity ε(T, f) and losses tangent tanδ(T, f) measured around room temperature. The increase of the amount of PbTiO3 in the ceramic samples causes sequential changes of their dielectric response from that typical for relaxor ferroelectric for x = 0 – 0.3 to ferroelectric-like with a diffuse phase transition for x = 0.4 - ~0.8 and, finally, to usual ferroelectric response for x = ~0.8 – 1. The compositions with 0.20 < x < 0.40 show coexistence of both ferroelectric and relaxor properties. The temperature dependences of the TSDCs show pronounced maxima at temperatures T ≈ TC, T ∼ 100 K and T ∼ 300 K; the phenomena that are at the origin of the effects are discussed. Graphical abstract: Image 1